2016
DOI: 10.1088/0957-4484/27/14/145702
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetic anisotropy enhancement in size controlled Ni nanowires electrodeposited into nanoporous alumina templates

Abstract: A large enhancement of the magnetic anisotropy of Ni nanowires (NWs) embedded in anodic aluminium oxide porous membranes is obtained as a result of an induced magnetoelastic (ME) anisotropy contribution. This unusual large anisotropy enhancement depends on the diameter of the NWs and exceeds the magnetostatic (MS) contribution. As a consequence, it leads to effective magnetic anisotropy energies as large as 1.4 × 10(6) erg cm(-3), which are of the same order of magnitude and comparable to the MS energies of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As expected, H MC is negative and increases toward the observed limiting value for pure Co networks with perpendicular c-axis as the Ni content is reduced. It is worth mentioning that the small negative anisotropy contribution observed for the Ni sample could be originated by residual stresses due to the reduced diameter of the nanowires, as recently suggested [87]. Figure 12e shows the anisotropic magnetoresistance ratio (AMR) vs. Ni content (x) at T = 20, 150 and 290 K for the different Ni x Co 1-x CNW networks (See [61,62] for more details on the estimation of AMR ratio in such CNWs).…”
Section: Interplay Between the Magnetic And Magneto-transport Propertmentioning
confidence: 66%
“…As expected, H MC is negative and increases toward the observed limiting value for pure Co networks with perpendicular c-axis as the Ni content is reduced. It is worth mentioning that the small negative anisotropy contribution observed for the Ni sample could be originated by residual stresses due to the reduced diameter of the nanowires, as recently suggested [87]. Figure 12e shows the anisotropic magnetoresistance ratio (AMR) vs. Ni content (x) at T = 20, 150 and 290 K for the different Ni x Co 1-x CNW networks (See [61,62] for more details on the estimation of AMR ratio in such CNWs).…”
Section: Interplay Between the Magnetic And Magneto-transport Propertmentioning
confidence: 66%
“…The general methods for synthesizing NiNWs are the template method and the chemical reduction method. 26 Tettamanti et al reported the incorporation of nickel nanowires in graphite-based composites to construct nanostructured platforms that are active in the nonenzymatic oxidation of ethanol. Carbon paste electrode material (CPE-NiNWs) demonstrated very good short-term stability, proving outstanding long-term stability, and allowing its use for at least 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel Nanowires (NiNWs) can be obtained by size modulation with a large aspect ratio, which makes it easier to form bridging structures in composite materials with reasonable electrical conductivity and high thermal and chemical stability. For nanostructured materials, changes in the microstructure have a significant effect on their properties. The general methods for synthesizing NiNWs are the template method and the chemical reduction method . Tettamanti et al reported the incorporation of nickel nanowires in graphite-based composites to construct nanostructured platforms that are active in the nonenzymatic oxidation of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, template-assisted electrodeposition is a popular way to obtain uniform and highly ordered nanowire arrays [12,13]. The nucleation and growth kinetics of the nanowire arrays in one-dimensional confined geometry can be tuned by different experimental parameters, including template dimension, electrolyte properties (pH value, composition, additive, and so on), reaction temperature, applied voltage, and the current density [14][15][16][17]. In our previous work, we demonstrated that current density can influence the growth direction and crystalline quality of electrodeposited semiconductor nanowire arrays, and further change their photoluminescence properties [18,19].…”
Section: Introductionmentioning
confidence: 99%